2011
DOI: 10.1111/j.1600-0536.2011.01900.x
|View full text |Cite
|
Sign up to set email alerts
|

Patch testing is a useful investigation in children with eczema

Abstract: We have shown that patch testing can identify relevant allergens in 44% of children with eczema. The commonest relevant allergens were medicament allergens, plant allergens, house dust mite, nickel, Amerchol® L101, and 2-bromo-2-nitropropane-1,3-diol. Patch testing can be performed in children as young as 2 years with the proper preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 10 publications
(10 reference statements)
0
17
0
Order By: Relevance
“…28 A single-center study of 110 British children found 10 positive reactions to DM (unspecified concentration), of which 8 had generalized and 1 had facial dermatitis. 32 However, an association with AD and the relevance of those reactions was not clearly demonstrated. A study of 571 patients found no association between DM 20% patch positivity and atopic history or characteristics of their eczema.…”
Section: Discussionmentioning
confidence: 99%
“…28 A single-center study of 110 British children found 10 positive reactions to DM (unspecified concentration), of which 8 had generalized and 1 had facial dermatitis. 32 However, an association with AD and the relevance of those reactions was not clearly demonstrated. A study of 571 patients found no association between DM 20% patch positivity and atopic history or characteristics of their eczema.…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum of contact allergens of adolescents is more similar to that of adults, including contact with occupational sensitisers. Patch testing in children is considered to be safe, and is recommended when allergic contact dermatitis is suspected or needs to be excluded, as in adults (119).…”
Section: Special Groupsmentioning
confidence: 99%
“…Moustafa et al recently published retrospective data supporting the relevance of positive patch tests in 44% of 110 children. Unfortunately, finding a positive allergen was not associated with improved clinical outcome in this population (Moustafa et al, 2011).…”
Section: Utility Of Patch Testingmentioning
confidence: 66%